Evaluating Potential Dryland Cropping Systems Adapted to Climate Change in the Central Great Plains. (1st November 2016) - Nielsen, David C.; Vigil, Merle F.; Hansen, Neil C.
Abstract : Climate in the semiarid central Great Plains is expected to become warmer and drier in coming decades, with potentially greater variability in precipitation and temperature. Cropping systems that include forages and allow flexibility for determining if a crop should be planted and which crop to plant (based on available soil water at planting) may provide the opportunity to maintain economic viability in a changing climate environment. The objective of this study was to compare cropping system productivity and profitability of flexible rotations that incorporate forages against grain‐based cropping systems that are set rotational sequences. Yield and net returns for five set rotations and three flexible rotations were compared at Akron, CO, over 5 yr. Winter wheat ( Triticum aestivum L.) yields were reduced by 57% when the fallow period prior to wheat production was replaced with crop production. Average net income was greatest for the continuously cropped all‐forage set 3‐yr rotation followed by the flexible 3‐yr rotations that included wheat and forage phases. The lowest net returns were seen for the set grain‐based rotations and the flexible wheat–grain crop rotation. Incorporating forage production as a phase in dryland wheat rotational systems can add profitability and sustainability to the production system in the face of climate variability. Core Ideas Including forages in semi‐arid dryland cropping systems increases profitability. Using flexible rotations based on soil water at planting can reduce fallow frequency. Continuously cropping with an all‐forage rotation maximizes net returns. Flexible rotations with forages may mitigate negative effects of climate variability.